PENGEMBANGAN PANTAI SINDHU SEBAGAI EKOWISATA BAHARI DI KAWASAN PANTAI SANUR BALI - Putu Agus Prayogi; I Made Suwitra Wirya; Ni Wayan Mekarini (Universitas Triatma Mulya, 2021)
This study aims to identify and analyze the existing tourist attractions in Sindhu Beach, starting from the internal aspects (strengths and weaknesses) and external aspects (opportunities and threats) and then formulates directions for optimizing the attractiveness of eco-marine tourism in an appropriate planning and strategy for Sindhu Beach to be an alternative to artificial nature tourism in Sanur Village. The method used is qualitative observational technic with SWOT Analysis to find out relevant strategies. From the analysis it can be seen that the general condition such as attractions, amenities, accessibility and additional services at Sindhu Beach.Eco Bahari is not well-developed yet. But the potency is still open wide to be eco-marine tourism spot based on internal and external factor especially the attraction side. Then the strategies that might be applied are (1) attractions optimalisation with turtle preservation nearby to educate visitors of environmental caring, (2) sharing information to local community about the eco-marine potency to add more beach value for people around, and (3) promote the beauty of Sindhu beach in social media so everybody know it well and attract them to visit it then